Mapping the glycan shields of enveloped viruses - Watanabe, Y (2020)
Glycosylation is a ubiquitous post-translational modification responsible for a multitude of crucial biological roles. As obligate parasites, viruses exploit host-cell machinery to glycosylate their own proteins during replication. Viral envelope proteins form a myriad of human pathogens including HIV-1, influenza virus, Lassa virus, coronaviruses, Zika virus, dengue virus, and Ebola virus have evolved to be glycosylated to varying degrees. These host cell derived glycans facilitate diverse structural and functional roles during the viral life-cycle ranging from aiding glycoprotein folding to enhancement of immune cell infection. As the primary focus of the humoral immune response, vaccine development efforts often concentrate on the viral glycoproteins that protrude from the virion envelope.